Effects of Strength Training on Dynamic Balance Among Pakistani Baseball Athletes - Sumbal; Tasleem Arif; Shamshaid Ahmed (The Sky)
The purpose of this study was to investigate Effect of strength on dynamic balance in Pakistan baseball Athletes. This study demonstrates how elite Pakistani baseball players’ dynamic balance could be improved after 12 weeks of strength training Pre/post intervention. The selected participants were divided into two groups, each with ten (10) members (the control group and the experimental group). The experimental group followed 12 weeks of strength training while the control group remains untreated. The participants’ dynamic balance was assessed using the Star Excursion Balance Test (SEBT). The experimental group’s dynamic balance improved significantly before and after intervention. According to these findings, 12 weeks of strength training had a substantial influence on dynamic balance of Pakistani baseball players. Furthermore, the strength training program had a significant and positive effect on dynamic balance of the Pakistani baseball participants. It is commended that the Pakistan baseball federation may introduce the strength training in every opportunity and focusing on dynamic balance to enhance the selected parameters of the baseball players of Pakistan. It would enhance the health of the athletes leading to the minimum performance